2012
DOI: 10.1097/mlr.0b013e31821d2b1d
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Data in Perinatal Population Health Databases

Abstract: This comprehensive collection of validation studies summarizing the quality of perinatal population data will be an invaluable resource to all researchers working with PHDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 204 publications
(200 citation statements)
references
References 58 publications
13
185
0
1
Order By: Relevance
“…17 Only factors that are well and accurately reported were included in the analyses. 16,[18][19][20][21][22] Missing data were infrequent, only 0.02% records were missing a gestational age and 0.02% were missing mode of onset of labor.…”
Section: Methodsmentioning
confidence: 99%
“…17 Only factors that are well and accurately reported were included in the analyses. 16,[18][19][20][21][22] Missing data were infrequent, only 0.02% records were missing a gestational age and 0.02% were missing mode of onset of labor.…”
Section: Methodsmentioning
confidence: 99%
“…Validation studies comparing these linked population datasets to medical records have shown that gestational age and jaundice are accurately reported. 35 We have also adjusted for a comprehensive list of known risk factors for jaundice. The limitations of the study include the calculation for LOS at birth; we were only able to calculate LOS in days rather than hours.…”
Section: Figurementioning
confidence: 99%
“…The accuracy and reliability of individual data items are typically reported. 3,4 The variables in perinatal population data can be continuous (e.g. gestational age), nominal (e.g.…”
Section: Abstract: Aimmentioning
confidence: 99%